STRATEGI PERAWATAN ROTATING EQUIPMENT SECARA BERKALA PADA POMPA TAGGING 4160 B PT. XYZ - Muhammad Rifki Rakhman; Ilham Arifin Pahlawan (ENIGMA: Engineering in Green Machinery, 2026)
PT. XYZ is a company engaged in palm oil processing that produces various derivative products, one of which is biodiesel. The reliability of this equipment determines operational efficiency, so an appropriate and sustainable maintenance strategy is needed. The author analyzed the periodic maintenance strategy on rotating equipment using direct field observation methods, interviews with technicians and equipment managers, and literature studies as a basis for comparison and validation. Based on the analysis results, it was found that several main causes of damage to rotating equipment are excessive vibration due to misalignment and unbalance, bearing damage due to inadequate lubrication, overheating of electric motors due to suboptimal cooling systems, and wear and tear of mechanical components due to service life and high workloads. To reduce the risk of downtime and increase the service life of the equipment, a periodic maintenance strategy was developed that includes condition monitoring as a measure for early detection of damage symptoms, preventive maintenance carried out routinely and scheduled to prevent damage, predictive maintenance based on the actual condition of the equipment through operational data analysis, and corrective maintenance as a corrective action when damage occurs.